PENGARUH NILAI AKUISISI DAN NILAI TRANSAKSI TERHADAP E-LOYALTY YANG DI MEDIASI OLEH E-SATISFACTION PADA E-COMMERCE SHOPEE DI KALANGAN MAHASISWA UNIVERSITAS SYIAH KUALA - Muhammad Nailan Edward; Sorayanti Utami (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
This study aims to measure the effect of the Acquisition Value and Transaction Value on E-Loyalty mediated by E-Satisfaction in the E-Commerce Shoppee among the Students of the Faculty of Economics and Business. The sample used in this study was 150 Economics and Business Faculty Students. Data collection equipment used in this study was a questionnaire. The sampling technique used is Non Probability Sampling, purposive sampling is used as an analytical method to determine the effect of all the variables involved. The results of this study indicate that the Acquisition Value and Transaction Value have a significant positive effect on E-Satisfaction and E-Loyalty, and also the results are obtained that E-Satisfaction mediates the relationship between Acquisition Value and E-Loyalty, and also mediates the relationship between Transaction Value and E- Loyalty.